Intercultural Communication - Ahrndt, Shannon (Open textbook library., 2020)
Intercultural Communication examines culture as a variable in interpersonal and collective communication. It explores the opportunities and problems arising from similarities and differences in communication patterns, processes, and codes among various cultural groups. It explores cultural universals, social categorization, stereotyping and discrimination, with a focus on topics including race, ethnicity, social class, religion, gender and sexuality as they relate to communication.